Pelatihan Pemanfaatan Whatsapp Business Untuk Meningkatkan Interaktifitas Komunikasi Dengan Pelanggan Bagi Anggota Hend'z Florist Aglonema - Yusmawati Yusmawati; Sultan Himawan; Teguh Tri Susanto (LPPM Universitas Bina Sarana Informatika, 2023)
Ornamental plants are plants that all parts are beautiful and attractive to look at, add to the beauty of the home page, office and can be placed indoors and have benefits for life. This makes people interested in cultivating ornamental plants. Ornamental plant cultivation is one of the business fields because many people have a hobby of maintaining ornamental plants. In recent years the trend of maintaining ornamental plants has mushroomed, especially since the Covid-19 pandemic because many activities outside the home are limited, making people bored and bored, giving rise to new hobbies, one of which is maintaining ornamental plants. The rise of the hobby of maintaining ornamental plants has made the ornamental plant business increasingly risen, it can be seen from the data on the number of requests that it provides a business opportunity for Indonesian ornamental plant entrepreneurs and farmers, especially the Depok area, West Java. One of them is Hend'z Floris Aglonema, which is a type of aglonema ornamental plant cultivation business. Based on the team's survey results regarding the problems faced by partners, partners are still not optimal in carrying out marketing communication activities, especially in optimizing the use of WhatsApp Business as a marketing communication medium. The team of advertising lecturers at the Faculty of Communication and Language, Bina Sarana Informatics University Jakarta seeks to provide a solution through community service activities in the form of WhatsApp Business Utilization Training to Increase Communication Interactivity with Customers for Members of Hend'z Florist Aglonema. This activity method is carried out face-to-face at Hend'z Florist Aglonema, the tutor team provides materials and training by demonstrating how to activate and use WhatsApp Business and participants will be directly involved in activating WhatsApp Business. The output form of this activity is a press release and the results of questionnaires from both partners and participants. Tanaman hias merupakan tanaman yang semua bagiannya bagus dan menarik untuk dilihat, menambah keindahan halaman rumah, kantor dan dapat ditempatkan dalam ruangan serta memiliki manfaat bagi kehidupan. Hal ini membuat masyarakat tertarik melakukan budidaya tanaman hias. Budidaya tanaman hias menjadi salah satu ladang bisnis karena banyaknya masyarakat yang memiliki hobi memelihara tanaman hias. Beberapa tahun ini tren memelihara tanaman hias menjamur, terutama semenjak pandemi covid-19 karena banyak aktifitas luar rumah dibatasi membuat masyarakat jenuh dan bosan sehingga memunculkan hobi baru yakni salah satunya adalah memelihara tanaman hias. Marakanya hobi memelihara tanaman hias menjadikan bisnis tanaman hias semakin bangkit, dapat dilihat dari data banyaknya permintaan sehingga memberikan sebuah peluang bisnis bagi para pengusaha dan petani tanaman hias Indonesia khsusunya daerah Depok Jawa Barat. Salah satunya adalah Hend’z Floris Aglonema, merupakan jenis usaha budidaya tanaman hias aglonema. Berdasarkan hasil survey tim mengenai permasalahan yang dihadapi oleh mitra adalah mitra masih belum optimal dalam melakukan kegiatan komunikasi pemasaran khususnya dalam mengoptimalkan pemanfaatan WhatsApp Business sebagai media komunikasi pemasaran. Tim dosen periklanan pada Fakultas Komunikasi dan Bahasa, Universitas Bina Sarana Informatika Jakarta berupaya memberi solusi melalui kegiatan pengabdian masyarakat berupa Pelatihan Pemanfaatan WhatsApp Business Untuk Meningkatkan Interaktifitas Komunikasi Dengan Pelanggan Bagi Anggota Hend’z Florist Aglonema. Metode kegiatan ini dilaksanakan secara tatap muka di Hend’z Florist Aglonema, tim tutor memberikan materi dan pelatihan dengan mendemonstrasikan mengenai cara mengaktifkan dan menggunakan WhatsApp Business dan peserta akan terlibat langsung mengaktifkan WhatsApp Business. Bentuk luaran kegiatan ini adalah press release dan hasil kuesioner baik dari mitra maupun peserta.